The characteristic of hulled barley varieties on economic-valuable traits - E. S. Doroshenko; E. G. Filippov (Зерновое хозяйство России)
The characteristic of hulled barley varieties on economic-valuable traits Barley is a universal agricultural grain crop, both in the distribution area and in diversified use. In recent years, the varieties of hulled barley together with the conventional unhulled varieties were introduced into the State List of Breeding Achievements of the Russian Federation. Grain of such varieties is more nutritious, as it contains larger amount of protein, vitamins, amino acids, etc. As there are no varieties of hulled barley in the State List of Breeding Achievements of RF on the Rostov region, the purpose to select varieties adapted to soil-climatic conditions of the North-Caucasus region is becoming more and more important [1]. The article presents the study results of more than 100 collection variety samples of spring hulled barley. The experiments were carried out on the fields of the department of barley breeding and seed-growing of the FSBSI “Agricultural Research Center “Donskoy” in 2014-2016. The lines and varieties “К-3426” (Japan), “К-3754” (Japan), “К-19109” (India), “К-26598” (Ethiopia), “E.E.A.N.46” (Bolivia), “Golozerny” (RF), “Golozerny 1” (RF), “Korona Laschego” (Poland), “Brunee” (Ethiopia) have been selected as the sources of fast ripening. The lines and varieties “К-266” (Pakistan), “К-26648” (Pakistan), “Nigohadaka” (Japan), “К-16535” (RF), “84469/70” (Czech Republic), “1218-524” (Czech Republic), “Buck CDC” (Canada) have been selected as the sources of large number of kernels per head. The lines and varieties “Dai-Mai” (Turkmenistan), “Аkkа” (Israel), “К-19103” (India), “К-3115” (Tajikistan), “К-3118” (Tajikistan) have been selected as the sources of productivity. The lines and varieties “Brunee” (Ethiopia), “S-264” (Mexico), “К-266” (Pakistan), “Omsky golozerny 1” (RF), “Yudinsky 1” (RF), “Аkkа” (Israel), “К-1328” (Turkey), “Kitaki-nadaka” (Japan), “К-3426” (Japan), “Komehadaka” (Japan) have been selected as the sources with high indexes of protein, lysine and starch. The following varieties “Brunee” (Ethiopia), “S-264” (Mexico), “К-266” (Pakistan), “Omsky golozerny 1” (RF), “Yudinsky 1” (RF), “Nigohadaka” (Japan), “Komehadaka” (Japan) have been selected due to a complex of the traits. All these varieties and lines have been recommended and are being used in the breeding programs while developing a new selection material of hulled barley, adapted to the increasing aridity of climate.